2007
DOI: 10.1158/0008-5472.can-06-3664
|View full text |Cite
|
Sign up to set email alerts
|

Human Tumor Xenografts Recurring after Radiotherapy Are More Sensitive to Anti–Vascular Endothelial Growth Factor Receptor-2 Treatment than Treatment-Naive Tumors

Abstract: The effects of antiangiogenic therapy on tumors relapsing after irradiation are not known. To this end, we irradiated human tumors growing s.c. in nude mice with a single dose of 20 or 30 Gy. Compared with primary (treatment-naive) xenografts, the growth rate of recurrent tumors was 1.6-fold slower, which is consistent with the known ''tumor bed effect.'' For similar size tumors, recurrences had fewer functional vessels, a reduced vessel coverage by perivascular cells, and were more necrotic. Placenta growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 23 publications
(25 reference statements)
1
23
0
Order By: Relevance
“…Radiation doses as low as 2 Gy could inhibit endothelial cell proliferation, survival, and invasion in vitro (40). As we showed that AZD6244 reduces the levels of VEGF that, when present, can protect from the damaging effects of radiation (21,22), the effect of combination therapy on vascular density and perfusion was assessed.…”
Section: Resultsmentioning
confidence: 86%
“…Radiation doses as low as 2 Gy could inhibit endothelial cell proliferation, survival, and invasion in vitro (40). As we showed that AZD6244 reduces the levels of VEGF that, when present, can protect from the damaging effects of radiation (21,22), the effect of combination therapy on vascular density and perfusion was assessed.…”
Section: Resultsmentioning
confidence: 86%
“…For example, an antibody to VEGF-receptor increased vascular basement membrane in a murine mammary carcinoma at three days after its administration, in concert with decreases in vascular density and vascular diameter (4). Other approaches to increase collagen could include local injection of collagen-based tissue fillers, as used in plastic surgery (47), or subcurative ionizing radiation (48) .…”
Section: Discussionmentioning
confidence: 99%
“…For example, both radiation treatment and chemotherapy can augment the sensitivity of tumor blood vessels to VEGF inhibition, which leads to increased growth delay of human tumor xenografts in combination therapy settings (99, 100). When administered using an MTD schedule, conventional chemotherapeutic drugs not only damage tumor cells; they also kill proliferating cells in normal tissues, which mandates the introduction of a drug-free recovery period between treatment cycles.…”
Section: Combination Of Anti-angiogenics With Conventional Cancer Trementioning
confidence: 99%